Negotiating National Languages, English as a World Language, and Individual Multilingualism in the Global South - May, S. (University of Jaffna, 2025)
In this keynote presentation, I will explore the often-fraught tensions in language policy in the global South in relation to the dominance of national languages and a related emphasis on public monolingualism, the burgeoning expansion and influence of English as a world language, and their collective impact on the maintenance of individual multilingualism. I will critically examine the still-apparent tendency in language policy – rooted in its colonial origins - to undermine individual multilingualism in a wide variety of local languages in favor of monolingualism in national languages and/or delimited bilingualism in an international language such as English. In so doing, I will also question the often-naïve assumption that the acquisition of English is the key to social, economic, and educational mobility in an increasingly globalized world.